Changes in cultivation parameters impact cytochrome P450 gene transcription in HepaRG cells: implications for in vitro toxicological assessments - Jochum, Kristina; Städele, Veronika; Marx-Stoelting, Philip (Frontiers in Pharmacology, 2025)
IntroductionThe HepaRG cell line has become a widely used model for liver toxicity testing due to the expression of cytochrome P450 enzymes essential for phase I metabolism of endogenous and exogenous compounds. As variations in expression may pose human health risks, determining CYP interactions of substances is crucial in toxicity assessments. Therefore, the use of human liver cell lines, such as HepaRG, for regulatory hazard assessment requires reproducible and stable CYP enzyme expression, despite possible influencing factors, such as seeding cell number, partial cell monolayer damage, and mRNA extraction timepoint.MethodsTranscriptional changes of 12 major CYP genes in relation to changes in cultivation parameters were investigated. To this end, HepaRG cells were cultivated according to two different methods and analyzed by RT-qPCR. Cells were seeded at five densities per cultivation method and mRNA was extracted at two timepoints after completion of differentiation, also comparing extracts from undamaged and intentionally damaged cell monolayers.ResultsA Bayesian regression model showed timepoint and cell number to have the most impact on transcription. Transcription was decreased at very high and very low cell numbers over recommended numbers, but this effect was strongly modulated by extraction timepoint, with transcription increasing after two additional weeks in culture. Intentional damage to the cell monolayer had marginal effects on transcription, and no evidence of an effect of cultivation method was found.ConclusionIn summary, extraction timepoint and seeding cell number are the two critical parameters to consider before initiating a CYP expression experiment with HepaRG cells.